How Work-life balance Mediates Social support and Gen Z Well-Being - Erik Irmansyah (Psychological Journal: Science and Practice, 2026)
Subjective well-being is an individual's evaluation of their life throughcognitive and affective aspects. For Generation Z employees, subjective well-being is important because this generation tends to prioritize work-lifebalance, mental health, and psychological comfort in the workplace. Theurgency of this research is related to the phenomenon of Generation Z beingvulnerable to work stress and having difficulty maintaining a balance betweenwork and personal life due to the development of digital technology. Onefactor contributing to subjective well-being is social support . However,previous research on the influence of social support on subjective well-beingstill shows inconsistent results. In addition, research on the role of work-lifebalance as a mediator in Generation Z employees in Indonesia is still limited.This study aims to examine the influence of social support on subjective well-being with work-life balance as a mediating variable in Generation Zemployees. The study used a non-experimental quantitative approach with apurposive sampling technique on 206 Generation Z employees aged 19–30years who have worked for at least one year. Data collection used theMSPSS scale to measure social support , WLBS to measure work-lifebalance , and BBC-SWB to measure subjective well-being . Data wereanalyzed using SEM-PLS. The results showed that social support had apositive and significant effect on subjective well-being , both directly andthrough work-life balance as a partial mediator. The implications of thisresearch demonstrate the importance of a supportive work environment inimproving the subjective well-being of Generation Z employees.